The Non-Zero Divisor Graph of Prime Ring - Majeed, Aliaa Aqeel; Aubad, Ali Abd; Kadem, Smeer (Iraqi Journal of Science, 2025)
uppose that  be a ring, the non-zero divisor graph of  denoted by  and defined as a simple graph has vertex set \{0,  and different vertices  are adjacent  if and only if    or . For the prime ring R, we aim to investigate the structure of the graph . This involved the behavior of the nilpotent elements of the prime ring inside the graph as well as proving the graph is connected with girth of three. Furthermore, characterize certain universal vertex in the graph.